Seroprevalence and determinants of risk of Hepatitis B and C Viral infections in blood donors: a cross sectional analytic study - Syed Abdul Mujeeb,1 and Mark S. Pearce.2,3 (Journal of Infection in Developing Countries, 2007)
Background: Pakistan has a high demand for safe blood, but a limited supply. This study was designed to identify the demographic determinants of safe donors. Methods: Demographic data on all donors of blood at a hospital-based blood bank were collected by questionnaire and samples tested for evidence of HBV, using agglutination tests (HBsAg Serodia kit) and HCV infection, using ELISA tests (Detect HCV TM V.3 kits).Results: Among the 21125 blood donors studied, seroprevalence of both HCV and HBV infection was 3.3%. Overall seroprevalence of either infection was 6.5%. However, the infection rate varied with differing donor characteristics; it was highest in donors who were illiterate, aged 30 years or above, or not resident within the city of Karachi. Conclusions: Using demographic characteristics may allow hospital-based blood banks to improve the safety of blood donations and reduce wastage of contaminated blood.